Turbulent Kinetic Energy and self-sustaining tones in an impinging jet using High Speed 3D Tomographic-PIV - Hassan H. Assoum; Mouhammad El Hassan; Jana Hamdi; Marwan Alkheir; Kamel Abed Meraim; Anas Sakout (Energy Reports, 2020)
Impinging jets are encountered in many ventilation systems, and these can have a major impact on the acoustic environment and energy performance. Self-sustaining tones produced by aero-acoustic coupling can occur in impinging jets when a feedback loop develops between the jet exit and the surface of impact. (Powell, 1964) developed an analogy that takes into account the sound sources created by vortices, and (Howe, 1975) was the first to use this analogy in the case of a near-wall flow. Howe's energy corollary makes it possible to calculate acoustic power using three quantities: vorticity, flow velocity and acoustic velocity, using experimental or numerical data and taking the aerodynamic field to be the main source of energy. In this study, the velocity and the acoustic fields in a rectangular jet impinging on a slotted plate were measured simultaneously using High Speed 3D Tomographic time-resolved particle image velocimetry (Tomographic-PIV) and a microphone. The 3D Tomographic time-resolved has the advantage of providing three components of velocity in a volume. Thus, we inspect the interaction between turbulent energy produced by the flow and the acoustic field in the presence of self-sustaining tones in order to have a better comprehension of the aero-acoustic coupling. Results were obtained for a Reynolds numbers Re = 5294 and Re = 5956 which are configurations that induces acoustic tones. The spectrum of the Turbulent Kinetic Energy (TKE) had peaks of frequencies such that the period of the acoustic signal was smaller than that of the TKE in presence of self-sustaining tones. The findings of this work may serve to develop new techniques of control to reduce the acoustic generation.
Keywords: 330; Aero-acoustic coupling; Impinging jet; Tomographic-PIV; Turbulent Kinetic Energy